Grandparents as the Primary Care Providers for Their Grandchildren: A Cross-Cultural Comparison of Chinese and U.S. Samples. (December 2019) - Wang, Chiachih DC; Hayslip, Bert; Sun, Qiwu; Zhu, Wenzhen
This study compared American and Chinese caregiving grandparents regarding variables reflecting challenges and resources in dealing with the demands of raising a grandchild. A total of 238 grandparent caregivers in the United States and 106 Chinese grandparent caregivers were sampled and completed research questionnaires for this study. Analyses indicated that after controlling for grandparents' gender, age, health, length of caregiving, and number of grandchildren, main effects for culture were significant for parental efficacy, authoritative parenting style, grandchild negative interpersonal dynamics, role satisfaction, well-being, and attachment to the grandchild. Correlational findings provided further understanding of cross-cultural similarities and differences in grandparent caregiving. Findings are discussed in the context of the globality of grandparent caregiving and the salience of family dynamic and values among Chinese grandparent caregivers. These findings also underscore the lack of supportive services for Chinese grandparents in light of their personal adaptive qualities and the demands of raising a grandchild.